DISINFESTATION OF MANGOES HADEN IN-FESTED BY Anastrepha fraterculus (WIED., 1830) (DIPTERA, TEPHRITIDAE), WITH GAMMA RADIATION (Brazilian Journal of Radiation Sciences, 2021)
The objective of experiment was determinate the radiation dose for disinfestation to mango Mangifera indica cv. Haden, infested by Anastrepha fraterculus larvae. For realization of the experiment, were collected fruits in the field, which were taking to Entomology laboratory where there was a infestation by the flies in cages during 72 hours period. Waited for the development of the larvae and before 5 – 8 days to infestation, the mangos were irradiated in a Cobalt-60 source with doses of: 0(control), 50, 100, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 1.100, 1.200 and 1.300 Gy. After the irradiation, the fruits were placed in climate chamber with 25 ±5°C of temperature and 70±5% of relative humidity, posteriorly waited the larvae exit to out of the fruit until the transformation in pupae and posteriorly in adult stage. By the results obtained our can concluded that the lethal dose to larvae in mangoes infested with 5-8 days after infestation were 600 Gy and 1.000 Gy (0.6 and 1 kGy) respectively. The dose of 50 Gy prevented the total adult emergence for both treatments.
Keywords: gamma radiation; fruit flies; mango